Factors related to self-management behavior among persons with mild-to-moderate chronic obstructive pulmonary disease in Wenzhou, China - Sheng Xiao-Wen; Samartkit Niphawan; Masingboon Khemaradee (Sciendo, 2023)
To describe the self-management (SM) behavior among persons with mild-to-moderate chronic obstructive pulmonary disease (COPD), and it examines the correlation between COPD knowledge, self-efficacy, perceived social support, and SM behavior among persons with mild-to-moderate COPD in Wenzhou, China.